The one - Cass, Keira (New York : HarperCollins Publishers, 2014)
"As her Selection approaches its finish, America must decide where her heart truly lies--and Prince Maxon must pick one winner to wear the crown"-- Provided by publisher.
Keywords: Marriage--Fiction.; Contests--Fiction.; Social classes--Fiction.; Princes--Fiction.; Love--Fiction.; Revolutionaries--Fiction.